EXPLORING SYNTACTIC COMPETENCE IN ACADEMIC WRITING: EVIDENCE FROM UINSU TADRIS ENGLISH STUDENTS - Anissa Anissa; Asti Ananta; Harshanda Rafika Putriana; Siti Ismahani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study investigates the syntactic competence of fifth-semester Tadris English students at Universitas Islam Negeri Sumatera Utara (UINSU) in producing academic writing. The purpose of this study is to identify common syntactic errors and examine students’ ability to apply syntactic structures accurately in academic texts. This research employed a qualitative descriptive approach involving 20 students as participants. The data were obtained from students’ academic writing assignments in the form of short essays and analyzed using error analysis techniques. The analysis focused on sentence structure, clause construction, subject–verb agreement, word order, and the use of connectors. The findings indicate that although students demonstrate basic understanding of English syntax, they still encounter difficulties in producing complex syntactic structures. Sentence structure errors, subject–verb agreement problems, and clause construction errors were the most frequently identified. These findings suggest that students have not fully mastered syntactic rules required for effective academic writing. Therefore, this study highlights the importance of explicit syntactic instruction, guided writing practice, and corrective feedback to enhance students’ syntactic competence in EFL academic contexts. ABSTRAK Penelitian ini bertujuan untuk mengkaji kompetensi sintaksis mahasiswa semester lima Program Studi Tadris Bahasa Inggris Universitas Islam Negeri Sumatera Utara (UINSU) dalam penulisan akademik. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan melibatkan 20 mahasiswa sebagai partisipan. Data diperoleh dari tugas menulis akademik mahasiswa berupa esai singkat yang dianalisis menggunakan teknik analisis kesalahan. Analisis difokuskan pada struktur kalimat, konstruksi klausa, kesesuaian subjek dan verba, urutan kata, serta penggunaan konjungsi. Hasil penelitian menunjukkan bahwa meskipun mahasiswa telah memiliki pemahaman dasar mengenai sintaksis bahasa Inggris, mereka masih mengalami kesulitan dalam menggunakan struktur sintaksis yang kompleks. Kesalahan yang paling sering ditemukan meliputi kesalahan struktur kalimat, kesesuaian subjek dan verba, serta konstruksi klausa. Temuan ini menunjukkan bahwa mahasiswa belum sepenuhnya menguasai kaidah sintaksis yang diperlukan dalam penulisan akademik. Oleh karena itu, penelitian ini menekankan pentingnya pengajaran sintaksis secara eksplisit, latihan menulis yang terarah, serta pemberian umpan balik untuk meningkatkan kompetensi sintaksis mahasiswa dalam konteks EFL.